An experimental investigation of a micro-tubular SOFC membrane-separated liquid desiccant dehumidification and cooling tri-generation system - Worall, Mark; Elmer, Theo; Riffat, Saffa; Wu, Shenyi; Du, Shangfeng (Elsevier, 2017)
This paper reports the results of experimental work carried out on a micro-tubular solid oxide fuel cell tri-generation systemthat uses the waste heat from the fuel cell for dehumidification and cooling though the integration of an open cycle liquid desiccant dehumidification and cooling system. The experimental results demonstrate regeneration of the potassium formate solution using the thermal output from the SOFC in the first of its kind tri-generation system. Optimisation has shown that a 2.2L.min-1 regenerator desiccant volumetric flow facilitates best performance.When integrated with the micro-SOFC, the open cycle desiccant system demonstrates a COP of approaching 0.7, an encouraging value for a waste heat driven cooling system of this capacity. A tri-generation performance analysis is presented which serves to demonstrate the novel system operating in a building. The system achieved an electrical efficiency of 11% and regeneration efficiency of approximately 37%. The electrical efficiency is lower than that predicted by the company supplying the micro-tubular SOFC, because the unit suffered sulphur poisoning during preliminary tests. The electrical power output decreased from 250W to 150W, which reduced the electrical efficiency from around 18% to 11% and the overall efficiency from approximately 45% to just over 37%. Low temperature (33-36°C) regeneration was demonstrated.